Optimization of the Tensile Properties of Polymeric Matrix Composites Reinforced with Magnetite Particles by Experimental Design (2020)
A full-factorial 33 experiment was used in this study to determine the optimal values of the tensile properties of three composite materials manufactured based on three polymeric resins: Derakane Momentum epoxy vinyl ester based on bisphenol-A (DM-411), polyester based on terephthalic acid (P115-A), and isophthalic polyester (P2000). Such materials were reinforced with magnetite powders at concentrations of 10, 20, and 30 wt %, and the particle sizes were classified with three sieves: #200 (46–75 μm), #325 (26–45 μm), and #500 (0–25 μm). The compounds were manufactured using the hand lay-up method at room temperature in accordance with ASTM D638-14 for M1-type specimens. A tensile test was conducted on a universal Microtest EM2/300/FR machine at a test speed of 5 ± 25 % mm/min using an Epsilon extensometer calibrated in accordance with the ASTM E83 standard at 20 ± 2 °C. The magnetite powders and compound morphology were studied by Scanning Electron Microscopy. The mechanical properties of the compounds and the optimal response found by Analysis of Variance (ANOVA) and Response Surface Methodology (RSM) are also reported. The best response to the mechanical stimuli occurs with the composite material prepared with the epoxy vinyl ester resin DM-411, a concentration of 29.4 % of magnetite (Fe3O4), a particle size of 58.5 microns, and a 200 sieve.